Construcción sociocultural de San Salvador de Jujuy, frontera simbólica de Argentina con Bolivia - Gaona, Melina (2017)
The city of San Salvador de Jujuy is analyzed both as a border space and as a city space. Through the systematization of local studies, the aim is to consider the historical, political, socioeconomic, migratory and symbolic elements that create the urban border experience. This contribution focuses on reconstructing the city as a network of senses. It deepens our understanding of migratory flows, the recent political situation, the impact of economic inequality on urbanisms, and the relevance of media and ritual acts in the configuration of dominant senses in cities. In addition, the factors that demarcate the difference and local inequality and the process of peripheralization and impoverishment of the soil are examined. Both the recent political conflicts that affect regional disarticulation and the symbolic disputes that cause tension in national belonging against a strong Andean influence are outlined